LOCAL SOLUTION A VISCOELASTIC NONLINEAR KIRCHHOFF'S SYSTEM WITH DISSIPATIVE TERM - Quispe Méndez, Teófanes (2010)
In present work, we study the existence and uniqueness of local solutions for the mixed problem relative to a system of viscoelastic nonlinear Kirchhoff's equation with dissipative term.